Discovery of the Sierra Pintada uranium District, Mendoza Province, Argentina - Féliz, rodrigo; Belluco, Alberto Esteban (International Atomic Energy Agency, 1981)
Fil: Féliz, rodrigo Comisión Nacional de Energía Atómica; Argentina